A Comparative Study of a Single-Cylinder 211cc Diesel Engine Performance Using B100 Biodiesel, Dexlite, and Pertamina Dex Fuels - Nurcahyadi, Teddy; Ramadhan, Naufal Hammam Maulana; Samputra, Muhammad Bagas Aji (JMPM (Jurnal Material dan Proses Manufaktur), 2025)
This study investigates the performance characteristics of a single-cylinder diesel engine fueled with Pertamina Dex, Dexlite, and B100 biodiesel. Experiments were conducted at 1000, 2000, 3000, and 4500 rpm to evaluate fuel mass flow rate, torque, brake power, BSFC, thermal efficiency, and engine temperature. The test range extends up to 4500 rpm, exceeding the engine’s 3600 rpm rated speed to specifically assess off-design performance and operational limits. The results show that each fuel exhibits a distinct performance profile. Dexlite delivers the highest torque and brake power at medium speeds. It also achieves the lowest BSFC and the highest thermal efficiency at 2000–3000 rpm. Pertamina Dex shows the most stable performance across all engine speeds, with relatively low fuel consumption and the lowest temperature rise, reflecting its refined hydrocarbon composition and high cetane number. B100 biodiesel displays higher mass flow rates and temperatures but demonstrates competitive thermal efficiency, particularly at low and high speeds, due to its oxygen-rich molecular structure that promotes complete combustion. These findings highlight that Dexlite is best suited for mid-speed efficiency-focused applications, Pertamina Dex delivers uniform and stable performance, and B100 offers combustion advantages under specific thermal and load conditions. This study offers guidance for selecting fuels that improve engine performance and support energy-efficient vehicle applications.